TINJAUAN PUSTAKA TENTANG KOMPETENSI BAHASA YANG PALING ESENSIAL DALAM KOMUNIKASI BISNIS GLOBAL - Hafizah Rifiyanti; Ari Kurniawan; Abdulah Rakhman (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This research addresses obstacles to effective English communication, focusing on essential language competencies—listening, speaking, reading, and writing—that are critical in global business. It explores which language skills are most important for international business communication and examines the impact of language proficiency on professional success. The goal of the study is to identify these key competencies for successful global business interactions and to provide insight into which skills professionals should focus on developing. To achieve this, a systematic literature review is conducted, establishing a structured theoretical framework by drawing on findings from previous research. The study concludes that essential language competencies for global business success include verbal communication, writing skills, cross-cultural understanding, listening, and negotiation abilities. Among these, verbal skills in English, as an international language, are especially crucial in settings such as presentations, meetings, and negotiations. Effective verbal communication requires not only mastery of grammar but also the ability to use non-verbal cues, like intonation and body language, to reinforce and clarify messages. These competencies are emphasized as crucial for professionals who wish to excel in the global business landscape, where effective communication can significantly influence outcomes. The findings suggest that developing both language and cultural understanding equips professionals to engage more effectively across linguistic and cultural boundaries, enhancing their ability to negotiate, collaborate, and succeed in diverse business environments.